USE OF COPPER SULFATE FOR DEHYDRATION OF INDUSTRIAL ALCOHOL - Reyna Mariñas, Leoncio (2007)
The objective of the work is to obtain alcohol dehydrated from rectified alcohol industrialist of 96º G.L., using copper sulphate, second composed was selected to make the work by its easy separation and recovery. The time required for the total dehydration of the alcohol was 60 minutes. The purity of the dehydrated alcohol was verified by measurement of its refractive index and by comparison with a pattern MERCK and 100 G.L. to 24ºC.